State Council of the Russian Federation: results of the constitutional reform - Malyutin, Nikita S. (Journal of the Belarusian State University. Law, 2022)
This article analyses the consequences of the constitutional reform of 2020 in the Russian Federation, which enshrined the special constitutional status of the State Council of the Russian Federation. It previously functioned on the basis of a special decree of the President of the Russian Federation and performed exclusively advisory functions. The key research task is to compare the current (federal law) and the former (decree of the President of the Russian Federation) regulation of the institute of the State Council of the Russian Federation in order to identify trends in the legal status of the latter. The reasons expressed for the need to give the State Council of the Russian Federation the status of a specific constitutional body involved in ensuring the coordinated functioning of a unified system of public power are critically evaluated. The conducted research shows that, in fact, the constitutional reform concerned only the form of securing the status of the State Council of the Russian Federation, while retaining the main regulation substantially the same. In addition, the article concludes that a number of status problems related to the existence and activities of the State Council of the Russian Federation and previously repeatedly noted in the scientific literature, unfortunately, were not resolved during the large-scale reform of the legal regulation of these relations.
Keywords: Russian Federation; constitutional reform; public authority; State Council of the Russian Federation; President of the Russian Federation